2019
DOI: 10.1007/s11149-019-09397-6
|View full text |Cite
|
Sign up to set email alerts
|

PV adoption: the role of distribution tariffs under net metering

Abstract: The deployment of decentralized productions units (DPU) like rooftop solar panels is a major challenge for a transition towards greener energy sources. Under a net metering system where the meter runs backward when there is excessive PV production, the electricity produced by a solar panel is valued at the retail price. Higher retail prices thus encourage the deployment of DPU. To identify this relationship, we use data from Wallonia where tariffs are paid on a mostly volumetric base and where there are 13 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…This finding is in line with that of Borenstein who found that the residential tariff design can influence households' solar PV adoption [41]. This finding is also consistent with Gautier and Jacqmin who found that higher tariffs under NET do not lead to investments in larger solar PV panels [42].…”
Section: Appendix A: Techno-economic Datasupporting
confidence: 91%
“…This finding is in line with that of Borenstein who found that the residential tariff design can influence households' solar PV adoption [41]. This finding is also consistent with Gautier and Jacqmin who found that higher tariffs under NET do not lead to investments in larger solar PV panels [42].…”
Section: Appendix A: Techno-economic Datasupporting
confidence: 91%
“…Various methods have been explored in all the previous works, e.g., capacity or demand tariffs (e/kW), volumetric tariffs (e/kWh), fixed tariffs (e/connection), or time-of-use (ToU) tariffs. In this regard, the analysis in [30] shows that, when applying volumetric distribution charges, in a setting where NM is in place, an increase in the distribution tariff leads to household PV deployment. In [31], the author demonstrates that a peak demand capacity tariff is more efficient and cost-reflective than its volumetric counterpart.…”
mentioning
confidence: 99%
“…A potential prosumer turns into an actual prosumer depending on the difference between the LVOE and the actual electricity costs without PV installation and on an exogenous probability. We use the results of Gautier and Jacqmin (2020) to calibrate this probability. On the basis of data from residential prosumers in Wallonia, these authors estimate, by means of an econometric analysis, the elasticity of investment in solar PV due to an increase in the volume-based tariff and, therefore, of the electricity price.…”
Section: Model Descriptionmentioning
confidence: 99%
“…where α is the exogeneous probability mentioned in Section 4.1, which is calibrateded to ensure that 1€cent induces an investment in PV of 8% as observed in Gautier and Jacqmin (2020). Finally, we can draw a random variable β i,n ∈ {0, 1} for every potential prosumer at every time-step n.…”
Section: Investment Decision Processmentioning
confidence: 99%